Effects of unsymmetrical voltage sags on industrial adjustable speed drives - Petronijević Milutin P.; Mitrović Nebojša N.; Kostić Vojkan Z.; Banković Bojan G. (Serbian Journal of Electrical Engineering, 2009)
This paper researches unsymmetrical voltage sag influence on torque ripple in scalar controlled (V/Hz), rotor field oriented (RFO) and direct torque controlled (DTC) drives. Electric drives performance degradation during voltage sag mainly depends on the used control algorithm. Industrial drives with all three types control methods are experimentally tested. Experiments with digital observer's application confirm the proposed solution. .